Evaluation of Art Integrated Physics Learning in a STEAM Approach to Improve STEM Literacy and Student Creativity - Khadijah; Muhammad syafruddin Akmal; Hutri Handayani Isra (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach is a development of STEM learning that integrates elements of art to strengthen students' creativity and conceptual understanding. STEAM-based physics learning is considered to be able to overcome abstract physics characteristics, but its implementation requires an appropriate and comprehensive evaluation system. This study aims to evaluate the learning of art integrated physics in the STEAM approach reviewed from STEM literacy and student creativity. The research uses a qualitative descriptive approach through literature study and analysis of art project-based physics learning practices. Data was collected from national and international journal articles, reference books, and relevant learning documents. Data analysis techniques are carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the evaluation of STEAM-based physics learning is more effective using authentic assessments, such as performance assessments, project assessments, portfolios, and science arts products. The evaluation is able to represent the understanding of physics concepts in a contextual manner and increase STEM literacy and creativity of students. This research is expected to be a reference in the development of a STEAM-based physics learning evaluation model in high schools